2020
DOI: 10.1021/acs.jpcc.9b11579
|View full text |Cite
|
Sign up to set email alerts
|

NMR Crystallography of Aluminum Carbide: Impurities in the Reagent and Improved 27Al NMR Tensors

Abstract: The structure of aluminum carbide (from two different manufacturers) has been interrogated by 27 Al solid-state NMR in an effort to accurately characterize the material. Quadrupolar line shapes for 27 Al sites such as these are important to catalogue, as efforts are underway to employ NMR crystallography tools to understand and predict both solid-state structures and perturbations to these that are relevant to NMR analyses. Impurities present in both of the samples are revealed to be aluminum oxycarbides, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…MHz. 49,50 Hayes et al identified aluminum oxycarbide impurities with smaller CQs in their recent study of commercial Al4C3 so a related aluminum species is plausible here. 50 Another possibility is the tetrahedral aluminum nitride environment that appears at around 110-115 ppm in AlN and in aluminum oxynitrides with a CQ of a few MHz, consistent with the resonance observed here.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…MHz. 49,50 Hayes et al identified aluminum oxycarbide impurities with smaller CQs in their recent study of commercial Al4C3 so a related aluminum species is plausible here. 50 Another possibility is the tetrahedral aluminum nitride environment that appears at around 110-115 ppm in AlN and in aluminum oxynitrides with a CQ of a few MHz, consistent with the resonance observed here.…”
Section: Resultsmentioning
confidence: 72%
“…49,50 Hayes et al identified aluminum oxycarbide impurities with smaller CQs in their recent study of commercial Al4C3 so a related aluminum species is plausible here. 50 Another possibility is the tetrahedral aluminum nitride environment that appears at around 110-115 ppm in AlN and in aluminum oxynitrides with a CQ of a few MHz, consistent with the resonance observed here. [51][52][53][54] Note that the 27 Al signal from Nb2AlC covers a range of ~90-170 ppm, so the impurity at 115 ppm is less pronounced but it can be clearly seen as a shoulder that appears as the interval between scans increases ( Figure S2 depending on the preparation conditions, with NbCx (0.7 ≤ x < 1) yielding quadrupolar 93 Nb signals.…”
Section: Resultsmentioning
confidence: 72%
“…49,50 Hayes et al identified aluminum oxycarbide impurities with smaller CQs in their recent study of commercial Al4C3 so a related aluminum species is plausible here. 50 Another possibility is the tetrahedral aluminum nitride environment that appears at around 110-115 ppm in AlN and in aluminum oxynitrides with a CQ of a few MHz, consistent with the resonance observed here. [51][52][53][54] Note that the 27 Al signal from Nb2AlC covers a range of ~90-170 ppm, so the impurity at 115 ppm is less pronounced but it can be clearly seen as a shoulder that appears as the interval between scans increases (Figure S2).…”
Section: Resultsmentioning
confidence: 72%
“…4.5 MHz while Al4C3 has two Al sites with CQ magnitudes of 14-17 MHz. 49,50 Hayes et al identified aluminum oxycarbide impurities with smaller CQs in their recent study of commercial Al4C3 so a related aluminum species is plausible here. 50 Another possibility is the tetrahedral aluminum nitride environment that appears at around 110-115 ppm in AlN and in aluminum oxynitrides with a CQ of a few MHz, consistent with the resonance observed here.…”
Section: Resultsmentioning
confidence: 72%
“…49,50 Hayes et al identified aluminum oxycarbide impurities with smaller CQs in their recent study of commercial Al4C3 so a related aluminum species is plausible here. 50 Another possibility is the tetrahedral aluminum nitride environment that appears at around 110-115 ppm in AlN and in aluminum oxynitrides with a CQ of a few MHz, consistent with the resonance observed here. [51][52][53][54] Note that the 27 Al signal from Nb2AlC covers a range of ~90-170 ppm, so the impurity at 115 ppm is less pronounced but it can be clearly seen as a shoulder that appears as the interval between scans increases (Figure S2).…”
Section: Resultsmentioning
confidence: 72%